Telemedicine Sebagai Media Konsultasi Layanan Kesehatan Bagi Masyarakat di Wilayah Pesisir - Ian R Tofure; Baringga Aurico De Erwada; Abdul M Ukratalo (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2025)
Telemedicine has emerged as an innovative solution for providing healthcare services, particularly in coastal areas that often face limitations in access and medical facilities. In coastal regions, the main challenges include the long distance from healthcare centers, limited infrastructure, and difficulties in accessing adequate medical care. Telemedicine, by utilizing communication technology to deliver remote medical services, offers an effective way to address these barriers. The purpose of this study is to evaluate the implementation of telemedicine as a health consultation medium for communities in coastal regions. The method used is book reference (reference from books and research journals). The data collection techniques employed in this study include gathering literature, reading, sorting data, taking notes, identifying, and validating the accuracy of the data for subsequent use in analysis. The results of the study show that telemedicine has a very strong aspect related to communication. In terms of utility, telemedicine offers a significant solution to the problem of disparities in healthcare services by utilizing communication channels that transform how people interact in the context of healthcare. Through telemedicine, healthcare providers can reach patients located in distant or remote areas, thereby expanding access and improving the quality of care.